Analisis Kepercayaan Diri pada Korban Bullying - Moh Anang Zulqurnain; Mohammad Thoha (Universitas Islam Negeri Madura, 2022)
This research is motivated by the many acts of bullying among teenagers or students, this is due to the lack of teacher supervision of students against bullying so that it will have an impact on students' self-confidence. The purpose of this study was to determine the self-confidence of students who were victims of bullying at SMP Al-Hakim Sampang. Based on this, there are three research focuses that become the reference for this research study, namely: first, what is the description of bullying behavior at Al Hakim Sampang Junior High School? Second, how is the impact of bullying behavior on students' self-confidence at SMP Al Hakim Sampang? Third, have you tried to increase students' self-confidence due to bullying behavior at SMP Al Hakim Sampang?. This study uses qualitative research methods, data collection procedures used by researchers including interviews, observation, documentation. Meanwhile, the data analysis includes data reduction, data presentation, and conclusions. Then in the process of checking the validity of the research data through extended participation, persistence in the observation process, and finally through triangulation. The results of this study indicate that: First, the description of the bullying behavior of class VIII students, namely starting from continuous taunts, causing perpetrators of violence or physical bullying. The results of the questionnaire showed physical bullying behavior of 80 with a percentage of 54% more than other bullying behaviors, then verbal bullying with a score of 43 with a percentage of 29% being the second most bullying behavior, then rational bullying with a score of 16 percentages of 11%, in the last order electronic bullying/ cyber bullying with a score of 9 percentage 6%. Second, the impact of bullying behavior on students' self-confidence. The impact on children's self-confidence varies, such as children who like to be alone, are not enthusiastic about learning, are less active in class, never join other friends, often do not go to school and some even want to quit school. Third, the teacher's efforts to increase students' self-confidence due to bullying behavior at Al Hakim Sampang Junior High School, namely if someone commits bullying behavior, the teacher immediately calls the perpetrator or victim of bullying to handle it, for the victim is given motivation so that his confidence returns again and for the perpetrator is given a reprimand and given punishment according to the violation, so that bullying behavior does not happen again.